Laboratory chemical waste: hazard classification by GHS and transport risk - Cássio Giovanni; Fabio Luiz Navarro Marques; Wanda Maria Risso Günther (Universidade de São Paulo, 2021)
ABSTRACT OBJECTIVES: To identify and evaluate, based on the Globally Harmonized System of Classification and Labelling of Chemicals (GHS) and the legislation of the Agência Nacional de Transportes Terrestres (ANTT - National Agency for Terrestrial Transport), the hazards arising from chemical waste generated in research laboratories in the health area. METHODS: Chemical residues generated in two medical research laboratories of the Faculdade de Medicina da Universidade de São Paulo were inventoried, from November 2017 to April 2019, and classified according to the GHS (hazard statements) and the ANTT transport legislation (risk classes), to determine the dangers coming from the respective substances and mixtures. RESULTS: In total, we identified 40 substances or mixtures with classification by the GHS indicating 36 hazard statements, 27 of which related to human health. According to the legislation established by ANTT, we found 16 cases of hazard associated with flammability, 15 cases related to toxicity and 12 cases related to corrosivity. CONCLUSIONS: Chemical residues generated in the laboratories studied are diversified in terms of their hazard characteristics, implying the possibility of exposure to severe risks to workers, students and the environment. The correct identification of these residues is a primary factor for reducing exposure to risks.